Dearomative gem-diprenylation of hydroxynaphthalenes by an engineered fungal prenyltransferase. Issue 42 (27th September 2022) - Xu, Yuanyuan; Li, Dan; Wang, Wenxuan; Xu, Kangping; Tan, Guishan; Li, Jing; Li, Shu-Ming; Yu, Xia
Abstract : A new catalyst for regiospecific dearomative gem -diprenylation of α-hydroxynaphthalenes from the F253G mutant of the fungal prenyltransferase CdpC3PT. Abstract : Prenylation usually improves structural diversity and bioactivity in natural products. Unlike the discovered enzymatic gem -diprenylation of mono- and tri-cyclic aromatic systems, the enzymatic approach for gem -diprenylation of bi-cyclic hydroxynaphthalenes is new to science. Here we report an enzymatic example for dearomative C4 gem -diprenylation of α-hydroxynaphthalenes, by the F253G mutant of a fungal prenyltransferase CdpC3PT. Experimental evidence suggests a sequential electrophilic substitution mechanism. We also explained the alteration of catalytic properties on CdpC3PT after mutation on F253 by modeling. This study provides a valuable addition to the synthetic toolkit for compound prenylation and it also contributes to the mechanistic study of prenylating enzymes.